Chinese design code for slender reinforced concrete columns - How, Wei Min. (2013)
The purpose of this report is to study the behaviour of slender reinforced concrete columns based on design code of practice GB50010-2010, EC2, BS8110, and theoretical analytical methods of transformation concept and P-delta method to analyse the failure load capacity of the slender reinforced column. Assumed pin-ended slender columns subjected to short term uniaxial bending and axial loading are evaluated using analytical and experimental methods.